Lighting system design according to different standards in office building: A technical and economic evaluations - Wagiman, K. R.; Abdullah, M. N. (2018)
Lighting system is an important sub-system in office buildings. A good design can contribute energy saving and visual comfort to occupants. This paper presents a comparison of lighting system design according to different standards: European Standard EN12464-1 and Malaysian Standard MS1525 in terms of average illuminance level and illuminance uniformity. In the design, the illuminance measurement is according to the Illuminating Engineering Society of North America (IESNA) and the European Standard EN12464-1. Three types of luminaires are considered which are: T8, T5 and light emitting diode (LED) lamps. The technical and economic evaluations are taken into account in this paper. The technical evaluations are considered the number of luminaires, average illuminance level and illuminance uniformity. The energy consumption (EC) and lighting energy numeric indicator (LENI) are considered according to the European Standard EN15193. Meanwhile, the economic evaluation involves billings and luminaires costs and billing savings. The case study is an office room and it is modelled and simulated using DIALux software. The results show that the design according to the European Standard EN12464-1 with uniformity based method that used T5 lamps had contributed to the highest number of luminaires and costs. Whereas, the design according to the Malaysian Standard MS1525 with illuminance level based method that used LED lamps had contributed to the lowest number of luminaires and costs. Thus it can provide the higher billing savings. It can be concluded the LED has great potential to replace T8 and T5 lamps.